2009
DOI: 10.1007/s10863-009-9222-x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of antitumor α-lactalbumin—oleic acid complexes with artificial and natural membranes

Abstract: The specific complexes of human alpha-lactalbumin (alpha-LA) with oleic acid (OA), HAMLET and LA-OA-17 (OA-complexes), possess cytotoxic activity against tumor cells but the mechanism of their cell penetration remains unclear. To explore the molecular mechanisms underlying interaction of the OA-complexes with the cell membrane, their interactions with small unilamellar dipalmitoylphosphatidylcholine (DPPC) vesicles and electroexcitable plasma membrane of internodal native and perfused cells of the green alga C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…Similar results were obtained regarding the bactericidal activity and membrane depolarization effect of HAMLET, bovine -lactoglobulin and pike parvalbumin in complex with OA on S. pneumococci bacteria [40,64]. Accordingly, it has been proposed that once the complex has adsorbed to the plasma membrane, it is most likely internalized by nonspecific pinocytosis, while other mechanisms of endocytosis, such as receptor-mediated endocytosis have not been ruled out [65].…”
Section: Cellular Trafficking Of Hamletsupporting
confidence: 71%
See 3 more Smart Citations
“…Similar results were obtained regarding the bactericidal activity and membrane depolarization effect of HAMLET, bovine -lactoglobulin and pike parvalbumin in complex with OA on S. pneumococci bacteria [40,64]. Accordingly, it has been proposed that once the complex has adsorbed to the plasma membrane, it is most likely internalized by nonspecific pinocytosis, while other mechanisms of endocytosis, such as receptor-mediated endocytosis have not been ruled out [65].…”
Section: Cellular Trafficking Of Hamletsupporting
confidence: 71%
“…Regardless of the preparation method used in the different experiments, it has been shown that the cytotoxicity of the resulting complexes was similar to that of conventionally prepared HAMLET or BAMLET [30,36,48,49,54,[61][62][63][64][65].…”
Section: Methods Of Hamlet or Hamlet-analog Preparation In Vitromentioning
confidence: 99%
See 2 more Smart Citations
“…It is thus strongly suggested that the protein portion of HAMLET, GAMLET, and the other HAMLET-like protein-OA complexes probably works as a delivery carrier of the cytotoxic OA to tumor cells (30,38). It is becoming increasingly evident that not only the rigid native structures but also the flexible MG structures are biologically functional, and many of the functional MG states are related to translocations of proteins or hydrophobic ligands across membrane bilayers (56 -61), and the interaction of HAMLET with artificial and natural membranes has been reported (62)(63)(64). We thus conclude that the MG-like state in HAMLET, GAMLET, and the other related complexes plays a role in transferring the hydrophobic OA molecules into tumor cells across the cell membranes.…”
Section: Discussionmentioning
confidence: 99%